Penerapan Etika Bisnis Islam dan Implikasinya terhadap Keberlanjutan Usaha: Studi Kasus pada Live Streaming Tiktok UMKM Aglonema - Jati Imantoro; Ulil Albab (Bulletin of Community Engagement, 2026)
This study aims to analyze the reality of the application of Islamic business ethics in the practice of TikTok live streaming in MSMEs selling aglonema flowers in Batangharjo Batanghari, East Lampung, understand the process of meaning and negotiation of ethical values in the digital platform ecosystem, and identify its implications for business sustainability and social responsibility. The study used a qualitative approach of interpretive case studies with six informants, consisting of five owners and one live streaming host. Data was collected through in-depth interviews, live streaming observations, and documentation, then analyzed using Nvivo 12 Plus through a thematic coding process. The results of the study show that the principles of trust, honesty, quality transparency, fair prices, guarantees, and virtues in the form of education and polite communication are implemented in the digital transaction mechanism. These values are negotiated with algorithmic rules and platform policies without eliminating the moral commitment of business actors. The application of Islamic business ethics has been proven to contribute to the formation of trust and customer loyalty that supports business sustainability. This research confirms that Islamic business ethics can function as an operational foundation in live streaming commerce and contribute to the development of digital entrepreneurship studies based on religious values.